2014
DOI: 10.1371/journal.pone.0105894
|View full text |Cite
|
Sign up to set email alerts
|

The Cytosolic Domain of Pex22p Stimulates the Pex4p-Dependent Ubiquitination of the PTS1-Receptor

Abstract: Peroxisomal biogenesis is an ubiquitin-dependent process because the receptors required for the import of peroxisomal matrix proteins are controlled via their ubiquitination status. A key step is the monoubiquitination of the import receptor Pex5p by the ubiquitin-conjugating enzyme (E2) Pex4p. This monoubiquitination is supposed to take place after Pex5p has released the cargo into the peroxisomal matrix and primes Pex5p for the extraction from the membrane by the mechano-enzymes Pex1p/Pex6p. These two AAA-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…78 Its association with Pex22 stimulates the full E2 activity of Pex4. 79 Pex2, Pex10, and Pex12 form a sub-complex at the peroxisome membrane and regulate the stabilities of each other. 80,81 These three E3 ligases function cooperatively to ubiquitinate Pex5 at the conserved cysteine.…”
Section: Role Of Pex5 Ubiquitination In Peroxisome Biogenesismentioning
confidence: 99%
“…78 Its association with Pex22 stimulates the full E2 activity of Pex4. 79 Pex2, Pex10, and Pex12 form a sub-complex at the peroxisome membrane and regulate the stabilities of each other. 80,81 These three E3 ligases function cooperatively to ubiquitinate Pex5 at the conserved cysteine.…”
Section: Role Of Pex5 Ubiquitination In Peroxisome Biogenesismentioning
confidence: 99%
“…Arabidopsis PEX22 was identified via its PEX4-binding ability and can function in yeast when expressed together with Arabidopsis PEX4 (Zolman et al, 2005). Yeast PEX22 enhances PEX4 enzymatic activity (El Magraoui et al, 2014), and a T-DNA insertion upstream of the Arabidopsis PEX22 start codon exacerbates the peroxisomal defects of pex4-1 (Zolman et al, 2005).…”
Section: Roles For Ubiquitination In Receptor Recycling and Peroxin Dmentioning
confidence: 99%
“…PEX26 binds PEX1-PEX6 via PEX6 (Birschmann et al, 2003;Matsumoto et al, 2003;Goto et al, 2011). Unlike PEX22 enhancement of PEX4 activity (El Magraoui et al, 2014), tether binding decreases PEX1-PEX6 ATPase activity in yeast (Gardner et al, 2015). In addition to tethering PEX1-PEX6, mammalian PEX26 interacts with the PEX14 docking peroxin (Tamura et al, 2014), hinting that PEX26 may bridge the import and export machinery.…”
Section: Atp-dependent Receptor Retrotranslocationmentioning
confidence: 99%
“…The receptor-recycling step involves monoubiquitination of Pex5p at the conserved cysteine residue (Williams et al, 2007;Okumoto et al, 2011) and requires the action of a number of peroxins, including Pex1p, Pex4p, Pex6p, Pex15p and Pex22p (Koller et al, 1999;Collins et al, 2000;Platta et al, 2008;Rosenkranz et al, 2006). Several studies have shown that the ubiquitin-conjugating (E2) enzyme Pex4p is responsible for Pex5p monoubiquitination in the yeast Saccharomyces cerevisiae (El Magraoui et al, 2014;Williams et al, 2007;Platta et al, 2007). Pex4p associates with the peroxisomal membrane via its interaction with the membrane-bound Pex22p (Koller et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Pex4p associates with the peroxisomal membrane via its interaction with the membrane-bound Pex22p (Koller et al, 1999). However, Pex22p also acts as a co-activator of Pex4p, stimulating the E2 activity of Pex4p through an unknown mechanism (Williams et al, 2012(Williams et al, , 2013El Magraoui et al, 2014).…”
Section: Introductionmentioning
confidence: 99%